1 HOUR RD Survival Map / Shahriza Ilyana Ramli … [et al.] - Ramli, Shahriza Ilyana; Ahmad Zawawi, Azlyn; Ismail, Junaida; Azizan, Intan Syahriza; Mohd Yusof, Noorlailahusna; Sajahan, Mohamed Samsudeen; Rusli, Noorayuni
Systematic, specific and expedite report duty process Is pertinent in producing productive worker and supporting organizational resource savvy initiatives. Hence, 1 HOUR RD Survival MAP has been created in leveraging the report duty process. This external websites link has been initiated by lecturers from the Faculty of Administrative Science and Policy Studies (FSPPP), UiTM Kedah Branch It is a web based application assessable via Internet connectivity containing information and attachment that offer systematic guidance for the academic staff on the process, sequence and unit involved in completing the report duty process within the limeframe of 1 hour. It is designed in the form of an easy-to-understand and navigable external link